Path planning for mobile-anchor based wireless sensor network localization: Static and dynamic schemes - Erdemir, Ecenaz; Tuncer, T. Engin (Ad hoc networks, 2018)
In wireless sensor networks, node locations are required for many applications. Usually, anchors with known positions are employed for localization. Sensor positions can be estimated more efficiently by using mobile anchors (MAs). Finding the best MA trajectory is an important problem in this context. Various path planning algorithms are proposed to localize as many sensors as possible by following the shortest path with minimum number of anchors. In this paper, path planning algorithms for MA assisted localization are proposed for both static and dynamic schemes. These approaches use MAs by stopping at minimum number of nodes to cover the monitoring area with shortest path length. A novel node localization algorithm based on alternating minimization is proposed. The performances of the proposed path planning algorithms are compared with previous approaches through simulations. The results show that more sensors are localized with less anchors in a shorter path and time for both schemes.